(untitled) (CAHIERS MAGELLANES-NS, 2024)
AI-based advancement in Talent Acquisition and Workforce Management has substantially reshaped the Human Resource department. This paper aims at reviewing the literature on how AI can improve efficiency, accuracy, and decision-making processes in the HRM function. AI in some ways like ML, NLP, and predictive analytics makes the labor market more efficient, reduces bias and provides insights into the labor market trends. This in turn enhances the agility and robustness of the organization’s HR function since AI undertakes repetitive work, freeing up the HR professionals to implement strategic plans. However, the effects of ethical concern and/ or implementations of AI integration have to be looked into. The existing status of Artificial Intelligence in HRM is described in this paper along with their importance, potential issues with ethics, and potentialities for the future. It approves the fact of AI as the effective tool in the processes of HRM and gives the directions for its proper application. By now, everyone is aware of the advancements of AI, which has positively impacted the radical restructuring of most business operations, including HRM. Now, a day’s AI technologies are used in talent acquisition, and workforce management to strengthen its processes with the aim to improve outcomes or organizational performance. Considering the increased competition and efforts linked with the need of organizations to adapt to the current trends in the market, AI in HRM has become vital. The following paper aims at discussing the implementation of artificial intelligence in human resource management with the primary emphasis on the management of recruitment and employees’ staffing. The purpose is to briefly explain how AI is transforming these core HR activities, and outlining the pros and cons and the outlook for the future.